2018
DOI: 10.22336/rjo.2018.2
|View full text |Cite
|
Sign up to set email alerts
|

The role of Optical Coherence Tomography in optic neuropathies

Abstract: Optical neuropathies are neuro-ophthalmologic disorders, the main symptoms of which are the decrease of visual acuity and the alteration of the color vision. Optical coherence tomography has been one of the most important innovations in ophthalmology, which offered the possibility to analyze specific structures of the retina. Optical coherence tomography performs in vivo, real-time, noncontact scanning and provides cross-sectional and volumetric images with a resolution approaching that of histology. Optical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 41 publications
2
21
0
1
Order By: Relevance
“…Toxic optic neuropathy was the second most common condition which was encountered in this study. Past studies have also revealed reduced thickness of RNFL among the patients of toxic optic neuropathy which was supported by the present analysis as well 8 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Toxic optic neuropathy was the second most common condition which was encountered in this study. Past studies have also revealed reduced thickness of RNFL among the patients of toxic optic neuropathy which was supported by the present analysis as well 8 .…”
Section: Discussionsupporting
confidence: 90%
“…It is also useful in providing a non-invasive tool to diagnose a lot of neurological illnesses 7 . Patients with optic neuropathies also get benefit from this investigation technique both in terms of diagnosis and observing the response of treatment 8 . This multipurpose diagnostic modality has been utilized both in clinical settings and research purpose 9 .…”
Section: Introductionmentioning
confidence: 99%
“…11 In fact, it can be said with authority that this imaging tool is nowadays a routine part of ophthalmology practice to identify macular lesions. 12 The role of OCT is also pivotal in detecting other eye-related conditions like hyper-reflectivity due to macular telangiectasia type-2, 13 optic neuropathies, 14 and glaucomatous retinal nerve fiber layer loss. 15 Papilledema is a serious medical condition that leads to visual disturbances and occurs due to the optic disc's swelling because of increased intraocular pressure; 16,17 OCT technique can be used to measure the amount of optic disc edema in this condition.…”
Section: Ophthalmologymentioning
confidence: 99%
“…Optical coherence tomography (OCT) stands out from the available methods as it has been used for more than three decades (Petzold et al 2017). It involves a noninvasive cross‐sectional imaging of the retina to assess changes in the retinal nerve fibre layer (RNFL) and, in more recent studies (Iorga et al 2018; Pillay et al 2018), changes in the ganglion cell layer. The decrease in the RNFL thickness correlates with degenerative processes (Park et al 2014; Britze & Frederiksen 2018).…”
Section: Introductionmentioning
confidence: 99%